Interconnections between the cultural and creative industries and tourism: challenges in four Ibero-American capital cities - Henriques, Cláudia (2022)
Purpose - This paper aims to investigate the European and Latin America urban cultural policies that could enhance cultural and creative sustainable tourism products development. Design/methodology/approach - The methodological framework is based on a comparative case study regarding the importance, dynamics and policies associated to cultural and creative tourism in four Ibero-American cities, namely, Brasilia, Buenos Aires, Lisbon and Madrid. Findings - This exploratory analysis underlines the growing importance of cultural and creative tourism in the four capital cities. On one hand, cities reveal different tourism impacts and, on the other hand, they are associated to different cultural and creative sector structures. Cities cultural and creative performance put in evidence that sustainable cities index, global talent competitiveness index and cultural and creative cities monitor, tend to position Madrid in the first place followed by, Lisbon, Buenos Aires and Brasilia. Research limitations/implications - In general, and despite the importance of space in the creative process, there is little research on the geography of the creative industries and there is a lack of cross-country comparative studies so that it is difficult to assess the particularities of each model of creativity. Practical implications - Cities could enhance more efforts in investing, not only in the traditional cultural infrastructures but also on the new forms of culture, new technologies, new makers, new audiences based on their attributes, activities and labels, in a framework of urban sustainable policies based on "innovation," "inclusiveness" and "interconnectivity." Originality/value - The originality of the paper lies in the comparative analysis of four cities based on cultural and creative sector and tourism interconnections. Simultaneously, it lies in an exploratory model application.